Magnetic Nanoparticle Hyperthermia: Maximizing Specific Loss Power for Magnetic Hyperthermia by Hard–Soft Mixed Ferrites (Small 29/2018). Issue 29 (19th July 2018) - He, Shuli; Zhang, Hongwang; Liu, Yihao; Sun, Fan; Yu, Xiang; Li, Xueyan; Zhang, Li; Wang, Lichen; Mao, Keya; Wang, Gangshi; Lin, Yunjuan; Han, Zhenchuan; et al.
Abstract : In article number1800135, Hao Zeng and co‐workers design and develop biocompatible magnetic nanoparticles with maximized specific and intrinsic loss power, by alloying hard and soft ferrites to engineer their effective anisotropy. The very high intrinsic loss power enables a dilute solution of nanoparticles to be heated above the hyperthermia temperature within minutes at an ultralow AC magnetic field of 3 kA m −1 . Bone cement incorporating low dosage of nanoparticles is heated efficiently.